Petunjuk Praktikum Struktur dan Fungsi Tumbuhan untuk Meningkatkan Keterampilan Bepikir Kritis Siswa Kelas VIII SMP - Neni Hasnunidah; Undang Rosidin; Nina Kadaritna (Universitas Sebelas Maret, 2018)
The purpose of this research measures the validity and effectiveness of practical guide on the structure and function plant and the key that has been developed based on the Argument-Driven Inquiry Models. This research use 4-D models that are developed by Thiagarajan namely Design, Define, Develop, and Disseminate. The result of the research shows that the practical guide is proper to use as learning resource that validity average is 97% are considered theoretically feasible and student response average is 88% are considered very good. Improvement of critical thinking skill is shown with gain score of 0,40.